Transforming Strategy into Sustainable Business Models for Consortia in Emerging Industries: A Study of Cakra Donya Consortium - Dian Alanudin; Muhamad Gidry Abdurrazak (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
The Cakra Donya Consortium is a collaborative platform for brands interested in Misel, presenting a novel framework for participating brands that necessitates a suitable business model for sustained operation. This research presents a customized business model tailored to the consortium's unique requirements. The proposed model emphasizes two core activities within the Cakra Donya Consortium: Collaborative Sustainable Product Research and Development (R&D), and Collaborative Marketing. These activities are strategically crafted to capitalize on the tangible and intangible resources shared among consortium members. Moreover, the proposed organizational structure advocates for a flat hierarchy, ensuring unrestricted membership and empowering members to contribute to program formulation under a legally binding agreement. These initiatives are geared towards achieving desired outcomes, including accelerating co-product innovation and fostering sustainability-oriented brand knowledge across consortium members and affiliated entities, thereby reaching a broader consumer base.